Travelling with young children / Nazima Versay Kudus - Kudus, Nazima Versay (Academy of Language Studies, 2023)
In 2010, when my husband was on his sabbatical leave to the United Kingdom, he brought along our family. While we were there, we decided to do some traveling since we were in the region. Armed with three young children aged from 4 to 10 who had different behaviours ranging from obedient to active and inquisitive, we took them on a trip to Belgium, France, The Netherlands, Germany, Austria, Italy, Vatican City, Switzerland and Austria. Here I would like to share some tips that fellow parents can benefit from when travelling with young children. Long flights, road trips and bus travels can make children particularly restless. Thus it is important to keep them occupied and entertained. Before travelling think of suitable activities that can be done when in different modes of transportation. Examples of road trip games are ‘number plate game’ and ‘I spy’. If using a tour bus, allow your child to make friends with his or her age group. On long flights, other than enjoying the in-flight movies, bring along a light toy and occasionally engage your child in child friendly activities on iPad. Should your child have to use this gadget, put on a headphone on him or her so that the fellow passengers are not disturbed.